EKSISTENSI GURU DALAM PENGEMBANGAN KURIKULUM - Achruh P, Andi (Universitas Islam Negeri Alauddin Makassar, 2016)
A curriculum is as a guideline for teachers in implementing the learning programs in order to achieve the educational goal where the teacher teaches. The teachers as a professional worker are required to design, implement, and evaluate the results of their own works as well as possible. Teacher is one who knows the exact circumstances of the implementation of the applicable curriculum. In addition, teachers are responsible for creating the desired learning outcomes. Thus, teachers are always required to improve their capabilities in accordance with the development of curriculum, development of science and technology, and the development of society. Therefore, the mastery of the curriculum for teachers is an absolute thing and obligation.